APPLICATION OF BIOPORE INFILTRATION HOLE INNOVATION FOR WATERLOGGING REDUCTION IN URBAN AREAS: A CASE STUDY OF PANJER VILLAGE - Putra, Anak Agung Adi Wiryya; Wedananta, Kadek Adyatna; Pulasari, Luh Ayu Putri Wedayanti; Pradhana, I Putu Dharmawan; Ramadiansyah, Sahri Aflah (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
The community service activity which was carried out in the Panjer Traditional Village, Denpasar aims to help overcome flooding in the Panjer Traditional Village area by installing hundreds of biopore holes. Biopores are small holes made at the surface of the soil with the aim of increasing the soil's absorption of rainwater. This method was first developed by Dr. Kamir R. Brata from the Bogor Agricultural University (IPB) as a solution to overcome the problem of waterlogging and urban flooding. Biopore holes are made using special tools to drill the soil to a certain depth, usually filled with organic matter such as leaves or food scraps. This organic matter will then be broken down by soil microorganisms, creating empty spaces that increase soil porosity. The activity was carried out simultaneously with hundreds of students and lecturers of the Faculty of Engineering and Informatics, Universitas Pendidikan Nasional. There are 14 groups divided into this biopore hole installation activity. The installation locations are spread across several points starting from the Waturenggong Street area to the end of Jalan Tukad Yeh Aya. The main function of biopores is to increase the absorption of groundwater, so that it can help reduce the risk of flooding and waterlogging. In addition, biopores also function to improve soil structure and increase soil fertility by adding organic matter. Another benefit of biopores is that it helps the process of recycling organic waste into compost that is beneficial to plants.